2016
DOI: 10.1007/s00412-016-0610-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the lamin A and its mutants on nuclear structure, cell proliferation, protein stability, and mobility in embryonic cells

Abstract: LMNA gene encodes for nuclear intermediate filament proteins lamin A/C. Mutations in this gene lead to a spectrum of genetic disorders, collectively referred to as laminopathies. Lamin A/C are widely expressed in most differentiated somatic cells but not in early embryos and some undifferentiated cells. To investigate the role of lamin A/C in cell phenotype maintenance and differentiation, which could be a determinant of the pathogenesis of laminopathies, we examined the role played by exogenous lamin A and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…Lamin A/C is the nuclear skeleton responsible for maintaining and stabilizing the nuclear architecture (4144). Because interrupting FAK signaling resulted in nuclear deformity (Figure 2B), changes in lamin A/C expression levels were assessed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lamin A/C is the nuclear skeleton responsible for maintaining and stabilizing the nuclear architecture (4144). Because interrupting FAK signaling resulted in nuclear deformity (Figure 2B), changes in lamin A/C expression levels were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…A similar cytological phenomenon has been reported in previous studies (56), however the molecular mechanism has not been clearly elucidated. In addition, nuclear lobulation and distorted nuclear morphology have been reported in cells with the LNMA mutation or lamin A/C downregulation (4143). The LNMA mutation or lamin A/C downregulation has been shown to result in nuclear distortion with a pathogenic tendency to develop aging and senescence (8, 30, 42, 57).…”
Section: Discussionmentioning
confidence: 99%
“…We observed various responses of different cell lineages to similar treatments stimulating proosteogenic phenotype and to similar alterations of genetic background such as the introduction of LMNA R527C or LMNA R471C mutations. A recent study used three cell lines: normal human dermal fibroblast, HeLa and HEK 293 and suggested that less differentiated embryonic cells are very sensitive to lamin A imbalance, and its upregulation disturbs lamin C, which may influence gene expression and many regulatory pathways [46].…”
Section: Discussionmentioning
confidence: 99%
“…Mice expressing farnesylated versions of prelamin A in neuronal tissues exhibited esophageal achalasia and abnormal enteric neurons [79], indicating that inappropriate levels of normal lamina proteins can be disruptive, even to post-mitotic cells. Other cell types (HEK293, NHDF and HeLa) overexpressing wild-type LMNA exhibited lattice-like aggregates of the protein and redistribution of LMNC [80]. Overexpression of LMNC in otherwise healthy Drosophila melanogaster is stage-specific lethal [16] while overexpression of LMNB1 in HEK293 and neuronal cells results in nuclear stiffness and a phenotype of autosomal-dominant leukodystrophy (ADLD) [81].…”
Section: Lamina-associated Protein Accumulation In Neurodegenerative mentioning
confidence: 99%